Preparation and characterization of low-cost waterproofing sheets from NR-loaded clay. Issue 1 (1st January 2020) - Abd El Kader, M.M.; El Deeb, A.S.
ABSTRACT: The importance of polymers is comprised in their industrial and technological applications. A low-cost waterproofing product with good thermal insulation properties is the aim of this paper. Natural rubber (NR)/clay composite was prepared with different concentrations of clay (20, 40, 60, 80, 100, 150 and 200) phr. An experimental investigation was carried out to obtain low-cost construction material with desirable mechanical, thermal and waterproofing properties. The influences of clay loading on mechanical, water absorption, swelling, specific gravity and thermal properties were inspected. It was observed that the incorporation of clay into the NR increases the thermal conductivity, the maximum degree of swelling and swelling index decrease with increasing clay content. The tensile properties of NR composite were found to be increased with the increase of clay content due to the increase of crosslinking density the incorporation of clay into the NR decreases the swelling parameters, Crosslink density calculations from both swelling and mechanical measurements have the same trend and order of magnitude. It exhibited some extent of improvement in tensile, hardness and compression set properties with the addition of clay. NR loaded with 60 phr clay was chosen as the reasonable value of thermal conductivity which lies in the range of thermal insulating material and suitable mechanical properties and other concentrations with the higher thermal conductivity can be used as a waterproofing sheet.